Улыбка Джоконды: книга о художниках / Юрий Безелянский - Безелянский Юрий Николаевич (Радуга, 1999)
Экземпляры: (20230623) / Инвентарный номер: 26443 / Цена: 30.00 / Сис.шифр: 85.143(3) / Авт.знак: Б 39 / ГРНТИ: 18 / ББК: 85.143(3)